(untitled) (Research, Society and Development, 2020)
Man, as a social being, needs a behavioral repertoire that guides his relations in society. This varied set of behaviors is called social skills, and can be learned throughout the life cycle. People with neurodevelopmental disorder have a deficit in social relationships as a prominent symptom, requiring reinforcing spaces that enable the construction of a socially skilled behavioral repertoire. Autistic Spectrum Disorder (ASD) has aroused the interest of several areas, however, the focus of studies remains in childhood. This study aimed to investigate possibilities of intervention with adults diagnosed with ASD, as a tool for social skills training (SST), a systematic attempt to teach strategies and interpersonal skills in order to improve the quality of the interactions that permeate interpersonal relationships. The methodology was based on a systematic review in the Virtual Health Library, by using the uni-terms “social skills”, “adults”, “autism”. Included were productions available in full, which presented interventions with adults with ASD and the development of social skills. The studies resulting from this selection were fully analyzed. The results discuss the effectiveness of interventions with this population for the development of social skills. It is concluded that SST is a possibility of effective intervention with atypical adults.